Testing our FAITHH: HIV stigma and knowledge after a faith-based HIV stigma reduction intervention in the Rural South. Issue 2 (1st February 2018) - Payne-Foster, Pamela; Bradley, Erin L. P.; Aduloju-Ajijola, Natasha; Yang, Xin; Gaul, Zaneta; Parton, Jason; Sutton, Madeline Y.; Gaskins, Susan
ABSTRACT: Eliminating racial/ethnic HIV disparities requires HIV-related stigma reduction. African-American churches have a history of addressing community concerns, including health issues, but may also contribute to stigma. We developed and pilot tested a faith-based, anti-stigma intervention with 12 African-American churches in rural Alabama. We measured HIV-related stigma held by 199 adults who participated in the intervention (individual-level) and their perception of stigma among other congregants (congregational-level). Analyses of pre- and post-assessments using a linear mixed model showed the anti-stigma intervention group reported a significant reduction in individual-level stigma compared with the control group (mean difference: −.70 intervention vs. −.16 control, adjusted p < .05). Findings suggest African-American churches may be poised to aid HIV stigma-reduction efforts.